Efficacy Evaluation of Fertilizers and Weed Control Practices to Mitigate Wheat Nutrient and Yield Losses - NADEEM,M.A. (2018)
ABSTRACT: Low fertilizer use efficiency due to inappropriate weed control practices is one of the main causes of poor wheat yield worldwide. A 2 year field experiment was conducted to study the effects of three fertilizer levels and four weed control practices on fertilizer use efficiency and nutrient uptake by wheat and its associated weeds. Fertilizer levels were F0 (zero fertilizer), F1 (75 kg ha-1 N + 50 kg ha-1 P2O5), and F2 (150 kg ha-1 N + 100 kg ha-1 P2O5) and weed control included W1 (weedy check), W2 (pendimethalin applied at 1,031 g a.i. ha-1), W3 (isoproturon + carfentrazone ethyl applied at 750 g a.i. ha-1) and W4 (manual weed control). Different weed control practices significantly reduced the NPK uptake by weeds and increased NPK uptake by wheat. Maximum uptake of NPK by wheat and minimum uptake by weeds were recorded in W4. Increasing dose of fertilizer increased NPK uptake by both weeds and wheat. However maximum fertilizer use efficiency and grain yield of wheat were achieved when highest dose of fertilizers (F2) was used along with manual weed control method (W4), which was followed by F2 and W3 during both years. We have come to the conclusion that to achieve higher wheat yield by increasing fertilizer doses, farmers should take appropriate weed control measures.